ELT in Covid-19-Augmented-Technological-Educational Ambience at the Private Universities in Bangladesh - Md. Nazmul Haque (LET: Linguistics, Literature and English Teaching Journal)
This study aims to examine obstacles the students encountered and the modifications they recommended in English language teaching and learning at private universities in Bangladesh during the COVID-19 pandemic. The mixed method approach comprised of both qualitative and quantitative research methods is applied in this study. The findings of the study show that all participants go through virtual English language learning during the COVID-19 lockdown. And the majority of them mention the difficulties of adopting a new approachin ELT suddenly including unstable network connections, costly internet data packages, unskilled teachers, load shedding, mental stress, teacher-students’ lack of technological skills, not having technological devices and sense of remoteness as the prevailing disadvantages during COVID-19. This study also recommends that university authorities should train students and teachers concerning technological devices. In addition, it also suggests that uninterrupted internet network and power supply, high-speed internet, and fair virtual assessment should be ensured. The prevalent result of the study is that online English language teaching and learning at private universities in Bangladesh require considerable pedagogical and technological modifications.